Job satisfaction and retension factors: strife and survival of CTE educators - Omar, Muhd Khaizer; Self, Mary Jo; Cole, Ki Lynn Matlock (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study focused on factors that affect whether or not CTE Educators stay in the teaching profession by using an online survey application with both quantitative and qualitative questions in a single design. From a population of 2607 teachers with valid email addresses, the total number of completed surveys was 623 participants. A two-phase of multiple linear regression was done. Five factors were found to be significant with the teachers’ retention plan: salary, administrative workloads, teachers’ evaluation, and assessment, motivation, and job satisfaction. A chi-square test was also done and showed significant relationships between the teachers’ age when entering the profession and their satisfaction with teaching. The findings contribute implications for educational stakeholders.